Irradiation Alters the Expression of MUC1, CD44 and Hyaluronan in Oral Mucosal Epithelium - Bina Kashyap; Konsta Naumanen; Jopi Mikkonen; Hannah Dekker; Engelbert Schulten; Elisabeth Bloemena; Sanna Pasonen-Seppänen; Arja Kullaa (Biomedicines, 2022)
Purpose: It is well established that cancer cells exploit aberrant synthesis of mucin 1 (MUC1) and hyaluronan (HA) synthesis along with HA’s physiological cell surface receptor CD44. However, their role in irradiated oral tissue has not been reported previously. We, therefore, aimed to study MUC1, CD44 and HA immunohistochemically in irradiated oral mucosa and their role in the long-term effects after radiotherapy. Materials and Methods: Oral mucosal biopsies were obtained from healthy subjects as controls and from patients after radiotherapy for head and neck cancer (irradiated group) during dental implant surgery. The presence of MUC1, CD44, and HA in oral mucosa was studied by immunohistochemical methods. The differences in the localization and intensity in the oral epithelium between control and irradiated tissue were analyzed. Results: The staining intensity of MUC1 was confined to the superficial epithelial layer, whereas HA and CD44 were found in the cell membranes in the epithelial basal and intermediate layers of control specimens. In irradiated epithelium, MUC1 staining was distributed throughout all the layers of the oral epithelium, with significant staining in the basal and intermediate layers. Accordingly, HA and CD44 staining extended to involve the superficial cells of the irradiated epithelium. The staining pattern of MUC1 and CD44 showed significant changes in irradiated samples. Conclusions: Our results showed that the staining intensities of MUC1, CD44, and HA were significantly elevated in irradiated tissue compared to controls. MUC1, CD44, and HA are important markers and take part in long-term changes in the oral mucosa after radiotherapy.